2005
DOI: 10.1007/s00432-005-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant CpG island methylation in early-onset sporadic gastric carcinoma

Abstract: Our results indicate that, unlike in colorectal carcinoma, APC and CTNNB1 mutations do not appear to be highly implicated in early-onset gastric carcinogenesis. In contrast, our data show that promoter methylation is a prevalent phenomenon in early-onset gastric carcinoma and may be related to gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…However, DNA methylation and histone deacetylation of DAPK1 have been found in colorectal and gastric cancers in association with silencing of this gene [22][23][24]. This discrepancy may reflect genetic instability at this site, changes in the balance of apoptosis, or the detected change in copy number may not lead to an increase in expression of the protein.…”
Section: Discussionmentioning
confidence: 84%
“…However, DNA methylation and histone deacetylation of DAPK1 have been found in colorectal and gastric cancers in association with silencing of this gene [22][23][24]. This discrepancy may reflect genetic instability at this site, changes in the balance of apoptosis, or the detected change in copy number may not lead to an increase in expression of the protein.…”
Section: Discussionmentioning
confidence: 84%
“…Frequency of promoter methylation in various genes in gastric carcinomaKang et al 2003;Esteller et al 2001a;Kim et al 2005 …”
mentioning
confidence: 99%
“…The current study found CIMP-H in 22% of GCs using four MINT genes MINT1, MINT2, MINT25 and MINT31 . In other studies, CIMP was de ned by the DNA methylation status of tumor-related genes, rather than MINT genes [18][19][20] -methylguanine DNAmethyltransferase was linked to the responsiveness of brain tumors to alkylating agents. These positive relationships between the DNA methylation of cancer-related genes and therapeutic ef cacy might be implicated in the longer survival time of GC patients with CIMP-H. Our data shows that the survival time of GC patients with CIMP-H is likely to be longer than those with CIMP-L/CIMP-N GCs, but no statistical differences were observed in survival time among patients with different CIMP status.…”
Section: Discussionmentioning
confidence: 99%